Composition for secondary battery electrode mixture layer and secondary battery electrode
The secondary battery electrode mixture layer composition, featuring a binder blend of crosslinked and non-crosslinked polymers, addresses the challenge of achieving high binding properties while ensuring coating properties, resulting in improved durability and cycle characteristics for secondary batteries.
Patent Information
- Application Number
- JP2023216096
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-05-23
- Filing Date
- 2023-12-21
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2039-05-23
AI Technical Summary
Existing secondary battery electrode mixture layers face challenges in achieving high binding properties while maintaining coating properties, particularly when using polymers with increased molecular weight.
A composition for a secondary battery electrode mixture layer is developed, incorporating a binder that combines a crosslinked polymer with a carboxyl group and a non-crosslinked polymer with a carboxyl group, where the non-crosslinked polymer is used in specific amounts to enhance binding properties without compromising coating properties.
The proposed composition achieves excellent binding properties and maintains the integrity of the electrode mixture layer, suppressing volume changes of active materials during charge and discharge, and enhancing the durability (cycle characteristics) of secondary batteries.
Smart Images

Figure 0007658414000001 
Figure 0007658414000002 
Figure 0007658414000003
Abstract
Description
[Technical field]
[0001] The present specification relates to a composition for a secondary battery electrode mixture layer and a secondary battery electrode. (CROSS REFERENCE TO RELATED APPLICATIONS) This application is a related application of Japanese patent application No. 2018-098419, filed on May 23, 2018, and claims priority to said Japanese application, the entire contents of which are incorporated herein by reference. [Background technology]
[0002] As secondary batteries, various electric storage devices such as nickel-hydrogen secondary batteries, lithium-ion secondary batteries, and electric double layer capacitors have been put to practical use. Electrodes used in these secondary batteries are prepared by coating and drying a composition for forming an electrode mixture layer containing an active material and a binder on a current collector. For example, in lithium-ion secondary batteries, an aqueous binder containing styrene butadiene rubber (SBR) latex and carboxymethyl cellulose (CMC) is used as a binder used in the negative electrode mixture layer composition. In addition, a binder containing an aqueous solution or aqueous dispersion of an acrylic acid-based polymer is known as a binder with excellent dispersibility and binding properties. On the other hand, an N-methyl-2-pyrrolidone (NMP) solution of polyvinylidene fluoride (PVDF) is widely used as a binder used in the positive electrode mixture layer.
[0003] In recent years, as the applications of various secondary batteries expand, there is a tendency for the demand for improved energy density, reliability, and durability to increase. For example, in order to increase the electric capacity of lithium-ion secondary batteries, specifications using silicon-based active materials as negative electrode active materials are increasing. However, it is known that silicon-based active materials have a large volume change during charging and discharging, and as they are used repeatedly, peeling or falling off of the electrode mixture layer occurs, resulting in a decrease in the capacity of the battery and a deterioration in cycle characteristics (durability). In order to suppress such defects, it is generally effective to increase the binding property of the binder, and studies on improving the binding property of the binder have been conducted in order to improve durability.
[0004] As a binder having good binding properties and effective in improving durability, a binder using the above-mentioned acrylic acid-based polymer has been proposed. Patent Document 1 describes that by using a polymer obtained by crosslinking polyacrylic acid with a specific crosslinking agent as a binder, it is possible to provide an electrode whose electrode structure is not destroyed even when an active material containing silicon is used. Patent Document 2 discloses a binder containing a crosslinked polycarboxylate and a linear polycarboxylic acid, and describes that this provides an active material layer that is highly durable against internal stress caused by volume expansion and contraction during charging and discharging. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2014 / 065407 [Patent Document 2] International Publication No. 2016 / 051811 Summary of the Invention
[0006] The binders disclosed in Patent Documents 1 and 2 are both capable of imparting good binding properties, but with improvements in the performance of secondary batteries, there is a demand for electrode mixture layers with higher binding properties. In general, in order to improve the binding property, it is effective to increase the molecular weight of the polymer that serves as the binder. However, when the molecular weight of the polymer is increased, the slurry viscosity of the electrode mixture layer composition also tends to increase, and as a result, the coatability is reduced, and there is a problem that a uniform electrode mixture layer cannot be obtained.
[0007] The present disclosure has been made in view of the above circumstances, and provides a composition for a secondary battery electrode mixture layer that can obtain a secondary battery electrode mixture layer having higher binding properties than conventional ones while ensuring coatability when a polymer having a carboxyl group, such as an acrylic acid-based polymer, is used as a binder. The present disclosure also provides a secondary battery electrode obtained by using the composition.
[0008] As a result of intensive research to solve the above problems, the present inventors have found that when a binder containing a specific amount of a non-crosslinked polymer having a carboxyl group is used for a crosslinked polymer having a carboxyl group, an electrode mixture layer having higher binding properties can be formed. According to the present disclosure, the following means are provided based on this finding.
[0009] [1] A composition for a secondary battery electrode mixture layer comprising a binder, an active material, and water, The binder includes a crosslinked polymer having a carboxyl group and a non-crosslinked polymer having a carboxyl group, A composition for a secondary battery electrode mixture layer, wherein the amount of the non-crosslinked polymer used is 0.1 mass % or more and 19.0 mass % or less based on the total amount of the crosslinked polymer and the non-crosslinked polymer. [2] The crosslinked polymer contains 50% by mass or more and 100% by mass or less of structural units derived from an ethylenically unsaturated carboxylic acid monomer based on the total structural units thereof, The non-crosslinked polymer contains 50% by mass or more and 100% by mass or less of structural units derived from ethylenically unsaturated carboxylic acid monomers relative to all structural units thereof. [3] The composition for a secondary battery electrode mixture layer according to [1] or [2], wherein the crosslinked polymer has a degree of neutralization of 75 mol % or more. [4] The composition for a secondary battery electrode mixture layer according to any one of [1] to [3], wherein the crosslinked polymer is obtained by using a crosslinkable monomer, and the amount of the crosslinkable monomer used is 0.1 mass % or more and 5.0 mass % or less based on the total constituent monomers of the crosslinked polymer. [5] The composition for a secondary battery electrode mixture layer according to any one of [1] to [4], wherein the non-crosslinked polymer has a weight average molecular weight of 10,000 or more. [6] A secondary battery electrode comprising a mixture layer formed on a surface of a current collector from the composition for a secondary battery electrode mixture layer according to any one of [1] to [5] above. Effect of the Invention
[0010] The composition for a secondary battery electrode mixture layer of the present disclosure has good coatability, and an electrode mixture layer formed from the composition and an electrode having the same have excellent binding properties and can maintain their integrity. Therefore, deterioration of the electrode mixture layer due to volume changes and shape changes of the active material accompanying charge and discharge is suppressed, making it possible to obtain a secondary battery with high durability (cycle characteristics).
[0011] Representative and non-limiting specific examples of the present disclosure will be described in detail below with reference to the drawings as appropriate. This detailed description is intended simply to provide those skilled in the art with details for implementing preferred examples of the present disclosure, and is not intended to limit the scope of the present disclosure. In addition, the additional features and disclosures disclosed below can be used separately or together with other features and disclosures to provide further improved secondary battery electrode mixture layer compositions and secondary battery electrodes.
[0012] In addition, the combinations of features and steps disclosed in the following detailed description are not essential to the implementation of the present disclosure in the broadest sense, but are described only to specifically illustrate representative embodiments of the present disclosure. Furthermore, the various features of the representative embodiments described above and below, and the various features of those described in the independent and dependent claims, do not have to be combined in the specific examples described herein or in the order listed to provide additional and useful embodiments of the present disclosure.
[0013] All features described in the specification and / or claims are intended to be disclosed individually and independently of one another as limitations to the original disclosure and claimed particulars, apart from any configuration of features described in the examples and / or claims. Furthermore, all numerical ranges and group or aggregate descriptions are intended to disclose their intermediate configurations as limitations to the original disclosure and claimed particulars. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The composition for secondary battery electrode mixture layer of the present disclosure (hereinafter also referred to as "the composition") may be in a slurry state that can be applied to a current collector, or may be prepared in a wet powder state so that it can be pressed onto the current collector surface. The secondary battery electrode of the present disclosure can be obtained by forming a mixture layer formed from the above composition on the surface of a current collector such as copper foil or aluminum foil.
[0015] The composition will be described below together with the components constituting the composition, and the secondary battery electrode obtained by using the composition will be described in detail. In this specification, "(meth)acrylic" means acrylic and / or methacrylic, "(meth)acrylate" means acrylate and / or methacrylate, and "(meth)acryloyl group" means acryloyl group and / or methacryloyl group.
[0016] The composition may include a binder, an active material, and water. The binder may include a crosslinked polymer having a carboxyl group and a non-crosslinked polymer having a carboxyl group.
[0017] <Crosslinked polymer having carboxyl groups> <Structural Unit Derived from Ethylenically Unsaturated Carboxylic Acid Monomer> The crosslinked polymer having a carboxyl group contained in the binder (hereinafter also referred to as "the crosslinked polymer") may have a structural unit derived from an ethylenically unsaturated carboxylic acid monomer (hereinafter also referred to as "component (a1)"). When the crosslinked polymer has a carboxyl group due to the structural unit, the adhesion to the current collector is improved, and the desolvation effect of lithium ions and ion conductivity are excellent, so that an electrode having low resistance and excellent high-rate characteristics can be obtained. In addition, water swelling is imparted, so that the dispersion stability of the active material in the mixture layer composition can be improved. The (a1) component can be introduced into the polymer by, for example, polymerizing a monomer containing an ethylenically unsaturated carboxylic acid monomer. Alternatively, it can be obtained by (co)polymerizing a (meth)acrylic acid ester monomer and then hydrolyzing it. Alternatively, it can be obtained by polymerizing (meth)acrylamide and (meth)acrylonitrile, etc., and then treating them with a strong alkali, or by reacting a polymer having a hydroxyl group with an acid anhydride.
[0018] Examples of the ethylenically unsaturated carboxylic acid monomer include (meth)acrylic acid, itaconic acid, crotonic acid, maleic acid, and fumaric acid; (meth)acrylamidoalkyl carboxylic acids such as (meth)acrylamidohexanoic acid and (meth)acrylamidododecanoic acid; ethylenically unsaturated monomers having a carboxyl group such as monohydroxyethyl succinate (meth)acrylate, ω-carboxy-caprolactone mono(meth)acrylate, and β-carboxyethyl (meth)acrylate, or their (partial) alkali neutralization products. One of these may be used alone, or two or more may be used in combination. Among the above, a compound having an acryloyl group as a polymerizable functional group is preferred, in that a polymer with a long primary chain length is obtained due to a high polymerization rate, and the binding strength of the binder is good, and acrylic acid is particularly preferred. When acrylic acid is used as the ethylenically unsaturated carboxylic acid monomer, a polymer with a high carboxyl group content can be obtained.
[0019] The content of the (a1) component in the present crosslinked polymer is not particularly limited, but may be, for example, 10% by mass or more and 100% by mass or less based on the total structural units of the present crosslinked polymer. By containing the (a1) component in such a range, excellent adhesion to the current collector can be easily ensured. The lower limit is, for example, 20% by mass or more, for example, 30% by mass or more, and for example, 40% by mass or more. When the lower limit is 50% by mass or more, the dispersion stability of the composition for the electrode mixture layer becomes good, and a higher binding force can be obtained, which is preferable, and may be 60% by mass or more, 70% by mass or more, or 80% by mass or more. The upper limit is, for example, 99.9% by mass or less, for example, 99.5% by mass or less, for example, 99% by mass or less, for example, 98% by mass or less, for example, 95% by mass or less, for example, 90% by mass or less, and for example, 80% by mass or less. The range can be an appropriate combination of these lower and upper limits, and can be, for example, 10% by mass or more and 100% by mass or less, for example, 50% by mass or more and 100% by mass or less, for example, 50% by mass or more and 99.9% by mass or less, for example, 50% by mass or more and 99% by mass or less, or for example, 50% by mass or more and 98% by mass or less.
[0020] <Other structural units> In addition to the component (a1), the crosslinked polymer may contain a structural unit derived from another ethylenically unsaturated monomer copolymerizable therewith (hereinafter also referred to as "component (b1)"). Examples of the component (b1) include structural units derived from an ethylenically unsaturated monomer compound having an anionic group other than a carboxyl group, such as a sulfonic acid group and a phosphoric acid group, or a nonionic ethylenically unsaturated monomer. These structural units can be introduced by copolymerizing an ethylenically unsaturated monomer compound having an anionic group other than a carboxyl group, such as a sulfonic acid group and a phosphoric acid group, or a monomer containing a nonionic ethylenically unsaturated monomer. Among these, as the component (b1), a structural unit derived from a nonionic ethylenically unsaturated monomer is preferred from the viewpoint of obtaining an electrode with good bending resistance, and (meth)acrylamide and its derivatives, etc., and nitrile group-containing ethylenically unsaturated monomers are preferred from the viewpoint of excellent binding property of the binder. In addition, when a structural unit derived from a hydrophobic ethylenically unsaturated monomer having a solubility in water of 1 g / 100 ml or less is introduced as the component (b1), it can exert a strong interaction with the electrode material and exhibit good binding properties to the active material. This is preferable because it is possible to obtain a firm and well-integrated electrode mixture layer. In particular, a structural unit derived from an alicyclic structure-containing ethylenically unsaturated monomer is preferable.
[0021] The ratio of the (b1) component to the total structural units of the crosslinked polymer can be 0% by mass or more and 90% by mass or less. The ratio of the (b1) component may be 1% by mass or more and 60% by mass or less, 2% by mass or more and 50% by mass or less, 5% by mass or more and 40% by mass or less, or 10% by mass or more and 30% by mass or less. In addition, when the (b1) component is contained at 1% by mass or more to the total structural units of the crosslinked polymer, the affinity to the electrolyte is improved, and therefore the effect of improving lithium ion conductivity can be expected.
[0022] Examples of (meth)acrylamide derivatives include N-alkyl (meth)acrylamide compounds such as isopropyl (meth)acrylamide and t-butyl (meth)acrylamide; N-alkoxyalkyl (meth)acrylamide compounds such as Nn-butoxymethyl (meth)acrylamide and N-isobutoxymethyl (meth)acrylamide; and N,N-dialkyl (meth)acrylamide compounds such as dimethyl (meth)acrylamide and diethyl (meth)acrylamide. One of these may be used alone, or two or more may be used in combination.
[0023] Examples of the nitrile group-containing ethylenically unsaturated monomer include (meth)acrylonitrile; (meth)acrylic acid cyanoalkyl ester compounds such as (meth)acrylic acid cyanomethyl and (meth)acrylic acid cyanoethyl; cyano group-containing unsaturated aromatic compounds such as 4-cyanostyrene and 4-cyano-α-methylstyrene; vinylidene cyanide; and the like. One of these may be used alone, or two or more may be used in combination. Among the above, acrylonitrile is preferred because of its high nitrile group content.
[0024] Examples of the alicyclic structure-containing ethylenically unsaturated monomer include cycloalkyl (meth)acrylate esters that may have an aliphatic substituent, such as cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, methylcyclohexyl (meth)acrylate, t-butylcyclohexyl (meth)acrylate, cyclodecyl (meth)acrylate, and cyclododecyl (meth)acrylate; isobornyl (meth)acrylate, adamantyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, dicyclopentanyl (meth)acrylate, and cycloalkyl polyalcohol mono(meth)acrylates such as cyclohexane dimethanol mono(meth)acrylate and cyclodecane dimethanol mono(meth)acrylate. One of these may be used alone, or two or more may be used in combination. Among the above, compounds having an acryloyl group as a polymerizable functional group are preferred in that a polymer with a long primary chain length is obtained due to a high polymerization rate, and the binding strength of the binder is improved.
[0025] As other nonionic ethylenically unsaturated monomers, for example, (meth)acrylic acid esters may be used. As the (meth)acrylic acid esters, for example, (meth)acrylic acid alkyl ester compounds such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate; Aromatic (meth)acrylic acid ester compounds such as phenyl (meth)acrylate, phenylmethyl (meth)acrylate, phenylethyl (meth)acrylate, and phenoxyethyl (meth)acrylate; (meth)acrylic acid alkoxyalkyl ester compounds such as 2-methoxyethyl (meth)acrylate and ethoxyethyl (meth)acrylate; Examples of the (meth)acrylic acid hydroxyalkyl ester compounds include hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, and hydroxybutyl (meth)acrylate, and one of these may be used alone or two or more may be used in combination. From the viewpoint of adhesion to the active material and cycle characteristics, aromatic (meth)acrylic acid ester compounds can be preferably used.
[0026] From the viewpoint of further improving lithium ion conductivity and high rate characteristics, compounds having an ether bond, such as (meth)acrylic acid alkoxyalkyl esters such as 2-methoxyethyl (meth)acrylate and ethoxyethyl (meth)acrylate, are preferred, and 2-methoxyethyl (meth)acrylate is more preferred.
[0027] Among nonionic ethylenically unsaturated monomers, compounds having an acryloyl group are preferred because they have a fast polymerization rate, resulting in a polymer with a long primary chain length, and because they provide good binding strength for the binder. As nonionic ethylenically unsaturated monomers, compounds having a homopolymer glass transition temperature (Tg) of 0° C. or less are preferred because they provide good bending resistance for the resulting electrodes.
[0028] The crosslinked polymer may be in the form of a salt in which a part or all of the carboxyl groups contained in the polymer are neutralized. The type of salt is not particularly limited, and examples thereof include alkali metal salts such as lithium, sodium, and potassium; alkaline earth metal salts such as calcium salts and barium salts; other metal salts such as magnesium salts and aluminum salts; ammonium salts, and organic amine salts. Among these, alkali metal salts and magnesium salts are preferred from the viewpoint of less adverse effects on battery characteristics, and alkali metal salts are more preferred.
[0029] The present crosslinked polymer is a crosslinked polymer having a crosslinked structure. The crosslinking method for the present crosslinked polymer is not particularly limited, and examples thereof include the following methods. 1) Copolymerization of crosslinkable monomers 2) Utilizing chain transfer to polymer chains during radical polymerization 3) After synthesizing a polymer having a reactive functional group, a crosslinking agent is added as necessary to perform post-crosslinking. Since the present crosslinked polymer has a crosslinked structure, a binder containing the crosslinked polymer or a salt thereof can have excellent binding strength. Among the above, the method of copolymerizing a crosslinkable monomer is preferred because the operation is simple and the degree of crosslinking can be easily controlled.
[0030] <Cross-linking monomer> Examples of the crosslinkable monomer include polyfunctional polymerizable monomers having two or more polymerizable unsaturated groups, and monomers having a self-crosslinkable crosslinkable functional group such as a hydrolyzable silyl group.
[0031] The polyfunctional polymerizable monomer is a compound having two or more polymerizable functional groups such as (meth)acryloyl group, alkenyl group, etc. in the molecule, and examples thereof include polyfunctional (meth)acrylate compounds, polyfunctional alkenyl compounds, compounds having both (meth)acryloyl group and alkenyl group, etc. These compounds may be used alone or in combination of two or more. Among these, polyfunctional alkenyl compounds are preferred in that they are easy to obtain a uniform crosslinked structure, and polyfunctional allyl ether compounds having multiple allyl ether groups in the molecule are particularly preferred.
[0032] Examples of the polyfunctional (meth)acrylate compound include di(meth)acrylates of dihydric alcohols such as ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, polyethylene glycol di(meth)acrylate, and polypropylene glycol di(meth)acrylate; tri(meth)acrylates of trihydric or higher polyhydric alcohols such as trimethylolpropane tri(meth)acrylate, tri(meth)acrylate of an ethylene oxide modified trimethylolpropane, glycerin tri(meth)acrylate, pentaerythritol tri(meth)acrylate, and pentaerythritol tetra(meth)acrylate; and poly(meth)acrylates such as tetra(meth)acrylate; and bisamides such as methylene bisacrylamide and hydroxyethylene bisacrylamide.
[0033] Examples of polyfunctional alkenyl compounds include polyfunctional allyl ether compounds such as trimethylolpropane diallyl ether, trimethylolpropane triallyl ether, pentaerythritol diallyl ether, pentaerythritol triallyl ether, tetraallyloxyethane, and polyallylsucrose; polyfunctional allyl compounds such as diallyl phthalate; and polyfunctional vinyl compounds such as divinylbenzene.
[0034] Examples of compounds having both a (meth)acryloyl group and an alkenyl group include allyl (meth)acrylate, isopropenyl (meth)acrylate, butenyl (meth)acrylate, pentenyl (meth)acrylate, and 2-(2-vinyloxyethoxy)ethyl (meth)acrylate.
[0035] Specific examples of the monomer having a self-crosslinkable crosslinkable functional group include a hydrolyzable silyl group-containing vinyl monomer, N-methylol (meth)acrylamide, N-methoxyalkyl (meth)acrylate, etc. These compounds can be used alone or in combination of two or more.
[0036] The vinyl monomer containing hydrolyzable silyl group is not particularly limited as long as it is a vinyl monomer having at least one hydrolyzable silyl group.For example, vinyl silanes such as vinyl trimethoxysilane, vinyl triethoxysilane, vinyl methyl dimethoxysilane, vinyl dimethyl methoxysilane, etc.; silyl group-containing acrylic acid esters such as trimethoxysilylpropyl acrylate, triethoxysilylpropyl acrylate, methyl dimethoxysilylpropyl acrylate, etc.; silyl group-containing methacrylic acid esters such as trimethoxysilylpropyl methacrylate, triethoxysilylpropyl methacrylate, methyl dimethoxysilylpropyl methacrylate, dimethyl methoxysilylpropyl methacrylate, etc.; silyl group-containing vinyl ethers such as trimethoxysilylpropyl vinyl ether, etc.; silyl group-containing vinyl esters such as vinyl trimethoxysilyl undecanoate, etc.
[0037] When the present crosslinked polymer is crosslinked by a crosslinkable monomer, the amount of the crosslinkable monomer used is preferably 0.05 parts by mass or more and 5.0 parts by mass or less, more preferably 0.1 parts by mass or more and 5.0 parts by mass or less, even more preferably 0.2 parts by mass or more and 4.0 parts by mass or less, and even more preferably 0.3 parts by mass or more and 3.0 parts by mass or less, based on 100 parts by mass of the total amount of monomers other than the crosslinkable monomer (non-crosslinkable monomers). If the amount of the crosslinkable monomer used is 0.05 parts by mass or more, it is preferable in that the binding property and the stability of the mixture layer slurry are better. If it is 5.0 parts by mass or less, the stability of the polymer tends to be higher. Similarly, the amount of the crosslinkable monomer used is preferably 0.02 to 0.7 mol %, and more preferably 0.03 to 0.4 mol %, based on the total amount of monomers other than the crosslinkable monomer (non-crosslinkable monomers).
[0038] <Particle size of crosslinked polymer having carboxyl group> In the mixture layer composition, it is preferable that the present crosslinked polymer is not present as large lumps (secondary aggregates) but is well dispersed as water-swellable particles having an appropriate particle size, since this allows the binder containing the crosslinked polymer to exhibit good binding performance.
[0039] The crosslinked polymer preferably has a particle size (water-swollen particle size) in the volume-based median size range of 0.1 μm or more and 10.0 μm or less when the crosslinked polymer has a neutralization degree of 80 to 100 mol% based on the carboxyl group and is dispersed in water. The particle size is more preferably in the range of 0.1 μm or more and 8.0 μm or less, even more preferably in the range of 0.1 μm or more and 7.0 μm or less, even more preferably in the range of 0.2 μm or more and 5.0 μm or less, and even more preferably in the range of 0.5 μm or more and 3.0 μm or less. If the particle size is in the range of 0.1 μm or more and 10.0 μm or less, the particles are present uniformly in a suitable size in the mixture layer composition, so that the mixture layer composition is highly stable and can exhibit excellent binding properties. If the particle size exceeds 10.0 μm or less, there is a risk that the binding properties will be insufficient as described above. In addition, it is difficult to obtain a smooth coating surface, and there is a risk of insufficient coatability. On the other hand, if the particle size is less than 0.1 μm, there is a concern from the viewpoint of stable production.
[0040] The particle size of the crosslinked polymer when dried (dry particle size) is preferably in the range of 0.03 μm to 3 μm in volumetric median size, more preferably 0.1 μm to 1 μm, and even more preferably 0.3 μm to 0.8 μm.
[0041] In the present crosslinked polymer, acid groups such as carboxyl groups derived from ethylenically unsaturated carboxylic acid monomers are neutralized so that the degree of neutralization is 20 mol% or more in the mixture layer composition, and the crosslinked polymer is preferably used in the form of a salt. The degree of neutralization is more preferably 50 mol% or more, even more preferably 70 mol% or more, even more preferably 75 mol% or more, even more preferably 80 mol% or more, and particularly preferably 85 mol% or more. The upper limit of the degree of neutralization is 100 mol%, or may be 98 mol% or 95 mol%. The range of the degree of neutralization can be appropriately combined with the above lower limit and upper limit, and may be, for example, 50 mol% or more and 100 mol% or less, 75 mol% or more and 100 mol% or less, or 80 mol% or more and 100 mol% or less. When the degree of neutralization is 20 mol% or more, it is preferable in that the water swelling property is good and the dispersion stabilization effect is easily obtained. In this specification, the neutralization degree can be calculated from the amount of a monomer having an acid group such as a carboxyl group and a neutralizing agent used for neutralization. The neutralization degree can be confirmed by measuring the powder of the crosslinked polymer or its salt after drying treatment at 80°C for 3 hours under reduced pressure conditions using IR, and by the intensity ratio of the peak derived from the C=O group of the carboxylic acid to the peak derived from the C=O group of the carboxylate.
[0042] <Method of producing crosslinked polymer having carboxyl group> The present crosslinked polymer can be prepared by known polymerization methods such as solution polymerization, precipitation polymerization, suspension polymerization, and emulsion polymerization, but precipitation polymerization and suspension polymerization (reverse phase suspension polymerization) are preferred from the viewpoint of productivity. Heterogeneous polymerization methods such as precipitation polymerization, suspension polymerization, and emulsion polymerization are preferred from the viewpoint of obtaining better performance in terms of binding property, etc., and among them, precipitation polymerization is more preferred. Precipitation polymerization is a method for producing polymers by carrying out a polymerization reaction in a solvent that dissolves the raw material unsaturated monomers but does not substantially dissolve the resulting polymer. As the polymerization proceeds, the polymer particles become larger through aggregation and growth, and a dispersion of polymer particles is obtained in which primary particles of tens to hundreds of nm are secondary aggregated to several μm to several tens of μm. A dispersion stabilizer can also be used to control the particle size of the polymer. The secondary aggregation can be suppressed by selecting a dispersion stabilizer, a polymerization solvent, etc. In general, precipitation polymerization in which secondary aggregation is suppressed is also called dispersion polymerization.
[0043] In the case of precipitation polymerization, the polymerization solvent may be selected from water and various organic solvents, etc., taking into consideration the type of monomer to be used, etc. In order to obtain a polymer having a longer primary chain length, it is preferable to use a solvent having a small chain transfer constant.
[0044] Specific polymerization solvents include water-soluble solvents such as methanol, t-butyl alcohol, acetone, methyl ethyl ketone, acetonitrile, and tetrahydrofuran, as well as benzene, ethyl acetate, dichloroethane, n-hexane, cyclohexane, and n-heptane, and these can be used alone or in combination of two or more. Alternatively, these can be used as a mixed solvent with water. In the present disclosure, the water-soluble solvent refers to a solvent having a solubility in water at 20° C. of more than 10 g / 100 ml. Of the above, methyl ethyl ketone and acetonitrile are preferred because they have good polymerization stability with little generation of coarse particles and little adhesion to the reactor, the precipitated polymer fine particles are not prone to secondary aggregation (or even if secondary aggregation does occur, it is easily disintegrated in an aqueous medium), they give polymers with small chain transfer constants and large degrees of polymerization (primary chain lengths), and they are easy to handle during the neutralization step described below.
[0045] The polymerization initiator may be any known polymerization initiator such as an azo compound, an organic peroxide, or an inorganic peroxide, but is not particularly limited. The conditions of use may be adjusted so that an appropriate amount of radicals is generated by known methods such as thermal initiation, redox initiation using a reducing agent, or UV initiation. In order to obtain a crosslinked polymer with a long primary chain length, it is preferable to set the conditions so that the amount of radicals generated is as small as possible within the allowable range of production time.
[0046] The amount of the polymerization initiator used is preferably, for example, 0.001 to 2 parts by mass, for example, 0.005 to 1 part by mass, or for example, 0.01 to 0.1 part by mass, when the total amount of the monomer components used is 100 parts by mass. If the amount of the polymerization initiator used is 0.001 part by mass or more, the polymerization reaction can be stably carried out, and if it is 2 parts by mass or less, a polymer having a long primary chain length is easily obtained.
[0047] The polymerization temperature varies depending on conditions such as the type and concentration of the monomers used, but is preferably 0 to 100° C., more preferably 20 to 80° C. The polymerization temperature may be constant or may vary during the polymerization reaction. The polymerization time is preferably 1 minute to 20 hours, more preferably 1 hour to 10 hours.
[0048] <Non-crosslinked polymer having carboxyl group> The composition contains a non-crosslinked polymer having a carboxyl group (hereinafter also referred to as "the non-crosslinked polymer") as a binder in addition to a crosslinked polymer having a carboxyl group. Like the crosslinked polymer, the non-crosslinked polymer may have a structural unit derived from an ethylenically unsaturated carboxylic acid monomer (hereinafter also referred to as "component (a2)"). The component (a2) and the method of introducing it are the same as those described for the component (a1) of the crosslinked polymer.
[0049] The content of the (a2) component in the present non-crosslinked polymer is not particularly limited, but in terms of solubility in water, it is preferably 50% by mass or more and 100% by mass or less, more preferably 60% by mass or more and 100% by mass or less, even more preferably 70% by mass or more and 100% by mass or less, and even more preferably 80% by mass or more and 100% by mass or less, based on all structural units of the present non-crosslinked polymer.
[0050] <Other structural units> In addition to the component (a2), the present non-crosslinked polymer may contain a structural unit derived from another ethylenically unsaturated monomer copolymerizable therewith (hereinafter also referred to as "component (b2)"). The component (b2) and the method for introducing it are the same as those described for the component (b1) of the present crosslinked polymer. The proportion of the (b2) component can be 0 mass% or more and 50 mass% or less, or may be 1 mass% or more and 40 mass% or less, or 2 mass% or more and 30 mass% or less, or 5 mass% or more and 20 mass% or less, based on all structural units of the polymer.
[0051] The non-crosslinked polymer may be in the form of a salt in which a part or all of the carboxyl groups contained in the polymer are neutralized. The type of salt is not particularly limited, and examples thereof include alkali metal salts such as lithium, sodium, and potassium; alkaline earth metal salts such as calcium salts and barium salts; other metal salts such as magnesium salts and aluminum salts; ammonium salts and organic amine salts. Among these, alkali metal salts and magnesium salts are preferred from the viewpoint of less adverse effects on battery characteristics, and alkali metal salts are more preferred.
[0052] In the present non-crosslinked polymer, acid groups such as carboxyl groups derived from ethylenically unsaturated carboxylic acid monomers are neutralized so that the degree of neutralization is 20 mol% or more in the mixture layer composition, and it is preferable to use it as a salt. The degree of neutralization is more preferably 50 mol% or more, even more preferably 70 mol% or more, even more preferably 75 mol% or more, even more preferably 80 mol% or more, and particularly preferably 85 mol% or more. The upper limit of the degree of neutralization is 100 mol%, and may be 98 mol% or 95 mol%. The range of the degree of neutralization can be appropriately combined with the above lower limit and upper limit, and may be, for example, 50 mol% or more and 100 mol% or less, 75 mol% or more and 100 mol% or less, or 80 mol% or more and 100 mol% or less. When the degree of neutralization is 20 mol% or more, it is preferable in that solubility in water is easily ensured. In this specification, the neutralization degree can be calculated from the amount of a monomer having an acid group such as a carboxyl group and a neutralizing agent used for neutralization. The neutralization degree can be confirmed by IR measurement of a powder of a crosslinked polymer or a salt thereof after drying treatment at 80°C for 3 hours under reduced pressure conditions, and the intensity ratio of a peak derived from a C=O group of a carboxylic acid to a peak derived from a C=O group of a carboxylate salt. The pH of the salt of the non-crosslinked polymer is, for example, pH 6.5 to 7.5, for example, pH 7 to 9, or for example, pH 8 to 10, when an aqueous solution is prepared by dissolving the salt in deionized water at a predetermined concentration (a specific concentration in the range of 0.2% by mass to 43% by mass shown in the examples), and the liquid temperature is adjusted to 25°C ± 1°C and then measured.
[0053] The weight average molecular weight (Mw) of the non-crosslinked polymer is not particularly limited, but is preferably 5,000 or more, more preferably 10,000 or more, in terms of obtaining an electrode mixture layer with excellent binding properties. Mw may be 100,000 or more, 500,000 or more, or 1,000,000 or more. The upper limit of Mw is not particularly limited, but may be, for example, 10,000,000 or less, or 5,000,000 or less, in terms of handling during production.
[0054] The binder used in the composition includes the present crosslinked polymer and the present non-crosslinked polymer. The amount of the present non-crosslinked polymer used is 0.1% by mass or more and 19.0% by mass or less with respect to the total amount of the crosslinked polymer and the non-crosslinked polymer. The amount of the non-crosslinked polymer used may be 0.5% by mass or more, 1.0% by mass or more, 2.0% by mass or more, or 3.0% by mass or more. The upper limit may be 18.0% by mass or less, 16.0% by mass or less, 14.0% by mass or less, or 12.0% by mass or less. The range may be a range that appropriately combines such lower and upper limits, for example, 0.5% by mass or more and 19.0% by mass or less, for example, 0.5% by mass or more and 18.0% by mass or less, or for example, 0.5% by mass or more and 14.0% by mass or less.
[0055] In this way, by using a specific amount (relatively small amount) of the present non-crosslinked polymer in combination with the present crosslinked polymer, it is possible to achieve higher binding properties than before. If the amount of the present non-crosslinked polymer used is 0.1 mass% or more, the effect can be achieved. If the amount of the present non-crosslinked polymer used exceeds 19.0 mass%, sufficient binding properties may not be obtained. In addition, by increasing the amount of the present non-crosslinked polymer used, the viscosity of the binder composition and the composition for electrode mixture layer can be reduced. Therefore, the present composition has a low viscosity, and it is possible to achieve improved binding properties while ensuring coatability.
[0056] <Method of producing non-crosslinked polymer having carboxyl group> The present non-crosslinked polymer can be prepared by using a known polymerization method such as solution polymerization, precipitation polymerization, suspension polymerization, or emulsion polymerization, and the polymerization method may be appropriately selected depending on the molecular weight, composition, and the like.
[0057] The polymerization initiator may be any known polymerization initiator such as an azo compound, an organic peroxide, an inorganic peroxide, etc., but is not particularly limited. The conditions of use can be adjusted so that an appropriate amount of radicals is generated by a known method such as thermal initiation, redox initiation using a reducing agent, UV initiation, etc. Furthermore, for the purpose of adjusting the molecular weight, etc., a known chain transfer agent may be used as necessary.
[0058] <Composition for secondary battery electrode mixture layer> The composition for a secondary battery electrode mixture layer of the present disclosure contains a binder, an active material, and water. The amount of the binder used in the composition is, for example, 0.1% by mass or more and 20% by mass or less, based on the total amount of the active material. The amount used is, for example, 0.2% by mass or more and 10% by mass or less, for example, 0.3% by mass or more and 8% by mass or less, and for example, 0.4% by mass or more and 5% by mass or less. If the amount of the binder used is 0.1% by mass or more, sufficient binding property can be obtained. In addition, the dispersion stability of the active material and the like can be ensured, and a uniform mixture layer can be formed. If the amount of the binder used is 20% by mass or less, the electrode mixture layer composition does not become highly viscous, and the coatability to the current collector can be ensured. As a result, a mixture layer having a uniform and smooth surface can be formed.
[0059] Among the above-mentioned active materials, lithium salts of transition metal oxides can be used as the positive electrode active material. For example, layered rock salt type and spinel type lithium-containing metal oxides can be used. Specific compounds of layered rock salt type positive electrode active materials include lithium cobalt oxide, lithium nickel oxide, and NCM{Li(Ni x ,Co y ,Mn z ), x+y+z=1} and NCA{Li(Ni 1-a-b Co a Al b )}, etc. Examples of the spinel-type positive electrode active material include lithium manganate, etc. In addition to oxides, phosphates, silicates, sulfur, etc. are used, and examples of the phosphates include olivine-type lithium iron phosphate, etc. As the positive electrode active material, one of the above may be used alone, or two or more may be combined to be used as a mixture or composite.
[0060] In addition, when a positive electrode active material containing a layered rock salt type lithium-containing metal oxide is dispersed in water, the lithium ions on the active material surface are exchanged with hydrogen ions in the water, and the dispersion liquid becomes alkaline. For this reason, there is a risk that aluminum foil (Al), which is a common positive electrode current collector material, may be corroded. In such a case, it is preferable to neutralize the alkali content eluted from the active material by using the unneutralized or partially neutralized present crosslinked polymer as a binder. In addition, it is preferable to use the unneutralized or partially neutralized present polymer in an amount such that the amount of unneutralized carboxyl groups in the present crosslinked polymer is equivalent to or greater than the amount of alkali eluted from the active material.
[0061] Since all positive electrode active materials have low electrical conductivity, they are generally used with the addition of a conductive assistant. Examples of the conductive assistant include carbon-based materials such as carbon black, carbon nanotubes, carbon fiber, graphite powder, and carbon fiber. Of these, carbon black, carbon nanotubes, and carbon fiber are preferred because they are easy to obtain excellent electrical conductivity. As carbon black, ketjen black and acetylene black are preferred. The conductive assistant may be one of the above alone or two or more may be used in combination. The amount of the conductive assistant may be, for example, 0.2 to 20% by mass, or, for example, 0.2 to 10% by mass, based on the total amount of the active material, from the viewpoint of achieving both electrical conductivity and energy density. The positive electrode active material may be surface-coated with a carbon-based material having electrical conductivity.
[0062] On the other hand, examples of the negative electrode active material include carbon-based materials, lithium metal, lithium alloys, and metal oxides, and one or more of these can be used in combination. Among these, active materials made of carbon-based materials such as natural graphite, artificial graphite, hard carbon, and soft carbon (hereinafter also referred to as "carbon-based active materials") are preferred, and graphite such as natural graphite and artificial graphite, and hard carbon are more preferred. In the case of graphite, spherical graphite is preferably used from the viewpoint of battery performance, and the preferred range of the particle size is, for example, 1 to 20 μm, and also, for example, 5 to 15 μm. In addition, in order to increase the energy density, metals or metal oxides capable of occluding lithium, such as silicon and tin, can also be used as the negative electrode active material. Among them, silicon has a higher capacity than graphite, and active materials made of silicon-based materials such as silicon, silicon alloys, and silicon oxides such as silicon monoxide (SiO) (hereinafter also referred to as "silicon-based active materials") can be used. However, while the silicon-based active material has a high capacity, it undergoes a large volume change during charging and discharging. For this reason, it is preferable to use it in combination with the carbon-based active material. In this case, if the amount of silicon-based active material is large, the electrode material may collapse, and the cycle characteristics (durability) may be significantly reduced. From this point of view, when the silicon-based active material is used in combination, the amount of the silicon-based active material is, for example, 60% by mass or less, or, for example, 30% by mass or less, relative to the carbon-based active material.
[0063] Since the carbon-based active material itself has good electrical conductivity, it is not necessary to add a conductive additive. When a conductive additive is added for the purpose of further reducing resistance, the amount of the conductive additive used is, for example, 10% by mass or less, or, for example, 5% by mass or less, based on the total amount of the active material, from the viewpoint of energy density.
[0064] When the composition for secondary battery electrode mixture layer is in a slurry state, the amount of active material used is, for example, in the range of 10 to 75 mass %, or, for example, in the range of 30 to 65 mass %, based on the total amount of the composition. If the amount of active material used is 10 mass % or more, migration of binders and the like is suppressed, and it is also advantageous in terms of the cost of drying the medium. On the other hand, if it is 75 mass % or less, the fluidity and coatability of the composition can be ensured, and a uniform mixture layer can be formed.
[0065] When preparing the electrode mixture layer composition in a wet powder state, the amount of the active material used is, for example, in the range of 60 to 97 mass % or, for example, in the range of 70 to 90 mass % based on the total amount of the composition. From the viewpoint of energy density, the amount of non-volatile components other than the active material, such as binders and conductive assistants, should be as small as possible within the range that ensures the necessary binding property and conductivity.
[0066] The composition for secondary battery electrode mixture layer uses water as a medium. In addition, for the purpose of adjusting the properties and drying property of the composition, it may be a mixed solvent with lower alcohols such as methanol and ethanol, carbonates such as ethylene carbonate, ketones such as acetone, tetrahydrofuran, N-methylpyrrolidone, and other water-soluble organic solvents. The proportion of water in the mixed medium is, for example, 50% by mass or more, and, for example, 70% by mass or more.
[0067] When the electrode mixture layer composition is in a coatable slurry state, the content of the water-containing medium in the entire composition can be, for example, in the range of 25 to 90 mass %, or, for example, in the range of 35 to 70 mass %, from the viewpoints of the coatability of the slurry, the energy cost required for drying, and productivity. When the electrode mixture layer composition is in a pressable wet powder state, the content of the medium can be, for example, in the range of 3 to 40 mass %, or, for example, in the range of 10 to 30 mass %, from the viewpoints of the uniformity of the mixture layer after pressing.
[0068] The composition may further use other binder components such as styrene / butadiene latex (SBR), acrylic latex, and polyvinylidene fluoride latex. When other binder components are used in combination, the amount of the binder components used may be, for example, 0.1 to 5% by mass or less, for example, 0.1 to 2% by mass or less, or for example, 0.1 to 1% by mass or less, based on the active material. If the amount of the other binder components used exceeds 5% by mass, the resistance increases, and high-rate characteristics may become insufficient. Among the above, styrene / butadiene latex is preferred in terms of excellent balance between binding property and flex resistance.
[0069] The composition for secondary battery electrode mixture layer of the present disclosure is obtained by mixing each component using a known means, which contains the above-mentioned active material, water, and binder as essential components. The method of mixing each component is not particularly limited, and a known method can be adopted, but a method of dry-blending powder components such as active material, conductive assistant, and binder, and then mixing with a dispersion medium such as water and dispersing and kneading is preferred. When the composition for electrode mixture layer is obtained in a slurry state, it is preferable to finish it into a slurry without poor dispersion or aggregation. As a mixing means, known mixers such as a planetary mixer, a thin film swirling mixer, and a self-revolving mixer can be used, but it is preferable to use a thin film swirling mixer in that a good dispersion state can be obtained in a short time. In addition, when using a thin film swirling mixer, it is preferable to perform preliminary dispersion in advance with a stirrer such as a disperser. The viscosity of the slurry, as Brookfield viscosity at 60 rpm, can be, for example, in the range of 500 to 100,000 mPa·s, for example, 500 to 10,000 mPa·s, for example, 500 to 5,000 mPa·s, for example, 500 to 3,000 mPa·s, or for example, 1,000 to 3,000 mPa·s. When the viscosity of the slurry is within the above range, good coatability can be ensured.
[0070] On the other hand, when the electrode mixture layer composition is obtained in a wet powder state, it is preferable to knead it to a uniform state without unevenness in concentration using a Henschel mixer, blender, planetary mixer, twin-screw kneader, or the like.
[0071] <Electrode for secondary batteries> The secondary battery electrode of the present disclosure comprises a mixture layer formed from the composition for secondary battery electrode mixture layer of the present disclosure on the surface of a current collector such as copper or aluminum. The mixture layer is formed by applying the composition to the surface of the current collector and then drying and removing the medium such as water. The method for applying the composition is not particularly limited, and known methods such as doctor blade method, dip method, roll coating method, comma coating method, curtain coating method, gravure coating method, and extrusion method can be adopted. In addition, the drying can be performed by known methods such as hot air blowing, reduced pressure, (far) infrared rays, and microwave irradiation. Usually, the mixture layer obtained after drying is subjected to a compression treatment using a mold press, a roll press, or the like. By compressing, the active material and the binder are brought into close contact with each other, and the strength of the mixture layer and its adhesion to the current collector can be improved. By compressing, the thickness of the mixture layer can be adjusted to, for example, about 30 to 80% of the thickness before compression, and the thickness of the mixture layer after compression is generally about 4 to 200 μm.
[0072] A secondary battery can be produced by providing the secondary battery electrode of the present disclosure with a separator and an electrolyte. The electrolyte may be in a liquid state or a gel state. The separator is disposed between the positive and negative electrodes of the battery, and serves to prevent short circuits caused by contact between the electrodes and to retain the electrolyte to ensure ionic conductivity. The separator is preferably a film-like insulating microporous membrane having good ion permeability and mechanical strength. Specific examples of the material that can be used include polyolefins such as polyethylene and polypropylene, and polytetrafluoroethylene.
[0073] The electrolyte may be any known electrolyte that is generally used depending on the type of active material. In lithium-ion secondary batteries, specific solvents include cyclic carbonates with high dielectric constants and high electrolyte dissolving ability, such as propylene carbonate and ethylene carbonate, and chain carbonates with low viscosity, such as ethyl methyl carbonate, dimethyl carbonate, and diethyl carbonate, which may be used alone or as a mixed solvent. The electrolyte is used by dissolving lithium salts, such as LiPF6, LiSbF6, LiBF4, LiClO4, and LiAlO4, in these solvents. In nickel-hydrogen secondary batteries, an aqueous potassium hydroxide solution may be used as the electrolyte. A secondary battery is obtained by storing a positive electrode plate and a negative electrode plate separated by a separator in a spiral or stacked structure in a case or the like.
[0074] As described above, the mixture layer formed from the composition for secondary battery electrode mixture layer disclosed in the present specification exhibits excellent binding properties with electrode materials and excellent adhesion with current collectors. Therefore, a secondary battery having an electrode with the mixture layer is expected to ensure good integrity and exhibit good durability (cycle characteristics) even after repeated charging and discharging, and is suitable for use as a secondary battery for vehicles, etc. The disclosure of the present specification also provides a method for producing a composition for a secondary battery electrode mixture layer, and a method for producing an electrode for a secondary battery. EXAMPLES
[0075] The present disclosure will be specifically described below based on examples. Note that the present disclosure is not limited to these examples. Note that, in the following, "parts" and "%" mean parts by mass and % by mass unless otherwise specified.
[0076] (Viscosity of 2% aqueous solution of this crosslinked polymer) The crosslinked polymer having a carboxyl group obtained in each of the following manufacturing examples was dissolved in deionized water to prepare an aqueous solution with a concentration of 2%. After adjusting the liquid temperature of the aqueous solution to 25°C ± 1°C, the viscosity of the 2% aqueous solution was measured using a B-type viscometer at 12 rpm.
[0077] (pH of crosslinked polymer) The crosslinked polymer having a carboxyl group obtained in each production example was dissolved in deionized water to prepare an aqueous solution with a concentration of 0.5%. The temperature of the aqueous solution was adjusted to 25°C ± 1°C, and then the pH was measured using a pH meter.
[0078] (pH of non-crosslinked polymer) Each non-crosslinked polymer used in Tables 2 and 3 was dissolved in deionized water to prepare an aqueous solution. The concentration of the non-crosslinked polymer in the aqueous solution is shown in Tables 2 and 3. The aqueous solution was adjusted to a liquid temperature of 25°C ± 1°C, and then measured with a pH meter.
[0079] (Aqueous solution viscosity of non-crosslinked polymer) The aqueous solution viscosity was measured in the same manner as for each of the crosslinked polymers used in Tables 2 and 3. The concentrations of the non-crosslinked polymers in the aqueous solutions are shown in Tables 2 and 3.
[0080] (Slurry Viscosity of Composition for Secondary Battery Electrode Mixture Layer) In addition, the secondary battery electrode mixture layer composition obtained in each of the following examples was adjusted to a liquid temperature of 25° C.±1° C., and then the slurry viscosity was measured with a Brookfield viscometer at 60 rpm.
[0081] <Production of the present polymer salt> (Production Example 1: Production of Carboxyl Group-Containing Crosslinked Polymer Salt R-1) For the polymerization, a reactor equipped with a stirring blade, a thermometer, a reflux condenser and a nitrogen inlet tube was used. Into the reactor, 567 parts of acetonitrile, 2.20 parts of ion-exchanged water, 100.0 parts of acrylic acid (hereinafter referred to as "AA"), 0.90 parts of trimethylolpropane diallyl ether (manufactured by Daiso Co., Ltd., trade name "Neoallyl T-20"), and 1.0 mol% of triethylamine relative to the AA were charged. After the inside of the reactor was sufficiently replaced with nitrogen, the inside temperature was raised to 55°C by heating. After confirming that the inside temperature was stable at 55°C, 0.040 parts of 2,2'-azobis(2,4-dimethylvaleronitrile) (manufactured by Wako Pure Chemical Industries, Ltd., trade name "V-65") was added as a polymerization initiator, and the reaction liquid became cloudy, so this point was determined as the polymerization initiation point. The polymerization reaction was continued while maintaining the inside temperature at 55°C by adjusting the external temperature (water bath temperature), and the inside temperature was raised to 65°C when 6 hours had passed from the polymerization initiation point. The internal temperature was maintained at 65°C, and cooling of the reaction solution was started 12 hours after the polymerization initiation point. After the internal temperature had dropped to 25°C, 52.4 parts of lithium hydroxide monohydrate (hereinafter referred to as "LiOH·H2O") powder was added. After the addition, stirring was continued at room temperature for 12 hours to obtain a polymerization reaction solution in the form of a slurry in which particles of the carboxyl group-containing crosslinked polymer salt R-1 (Li salt, neutralization degree 90 mol%) were dispersed in the medium.
[0082] The obtained polymerization reaction solution was centrifuged to settle the polymer particles, and the supernatant was removed. The precipitate was then redispersed in acetonitrile of the same weight as the polymerization reaction solution, and the polymer particles were precipitated by centrifugation and the supernatant was removed. This washing procedure was repeated twice. The precipitate was collected and dried at 80°C for 3 hours under reduced pressure to remove the volatile matter, obtaining a powder of carboxyl group-containing polymer salt R-1. Since carboxyl group-containing crosslinked polymer salt R-1 is hygroscopic, it was sealed and stored in a container with water vapor barrier properties. The powder of carboxyl group-containing polymer salt R-1 was subjected to IR measurement, and the degree of neutralization was calculated from the intensity ratio of the peak derived from the C=O group of the carboxylic acid and the peak derived from the C=O of the carboxylate Li, which was 90 mol%, equal to the calculated value from the charge. The viscosity of a 2% aqueous solution of carboxyl group-containing polymer salt R-1 was measured and found to be 2110 mPa·s.
[0083] (Production Examples 2 to 6: Production of Carboxyl Group-Containing Crosslinked Polymer Salts R-2 to R-6) The same operation as in Production Example 1 was carried out except that the types and amounts of the monomer, crosslinkable monomer, and neutralizing agent were as shown in Table 1, to obtain a polymerization reaction liquid containing carboxyl group-containing crosslinked polymer salts R-2 to R-6. Next, the same operation as in Production Example 1 was carried out for each polymerization reaction solution to obtain powdered carboxyl group-containing crosslinked polymer salts R-2 to R-6. Each carboxyl group-containing crosslinked polymer salt was stored in a sealed container having water vapor barrier properties.
[0084] [Table 1]
[0085] Details of the compounds used in Table 1 are shown below. AA: Acrylic acid DMAA: Dimethylacrylamide T-20: Trimethylolpropane diallyl ether (manufactured by Daiso Co., Ltd., product name "Neoallyl T-20")
[0086] (Electrode evaluation) The active material was graphite, or silicon particles and graphite, which are negative electrode active materials, and the binder was a carboxyl group-containing crosslinked polymer salt and a carboxyl group-containing non-crosslinked polymer. The coating property during the formation of the mixture layer and the peel strength between the mixture layer and the current collector (i.e., the binding property of the binder) were measured for the mixture layer composition. Natural graphite (manufactured by Nippon Graphite Co., Ltd., product name "CGB-10") was used as the graphite, and silicon particles (Sigma-Aldrich, Si nanopowder, particle size <100 nm) were used as the silicon particles.
[0087] Example 1 For 100 parts of natural graphite, 3.168 parts of powdered carboxyl group-containing polymer Li salt R-1 and 0.032 parts of non-crosslinked sodium polyacrylate (manufactured by Toagosei Co., Ltd., trade name "Aronvis SX") were weighed and mixed thoroughly in advance, and then 165 parts of ion-exchanged water was added and pre-dispersed with a disperser. Then, main dispersion was performed for 15 seconds using a thin film rotating mixer (manufactured by Primix Corporation, FM-56-30) at a peripheral speed of 20 m / sec to obtain a slurry-like composition for the negative electrode mixture layer. The slurry concentration (solid content) was calculated to be 38.5%. The viscosity of the slurry was 2800 mPa·s, which was a sufficiently low value. An electrode was produced using the obtained mixture layer composition, and the electrode was evaluated. The specific procedure and evaluation method are shown below.
[0088] <Preparation of negative electrode> The mixture layer composition prepared above was applied to a 20 μm thick copper foil (manufactured by Nippon Foil Co., Ltd.) using a variable applicator, and the mixture layer was formed by drying at 100°C for 15 minutes in a ventilated dryer. After that, the mixture layer had a thickness of 50±5 μm and a packing density of 1.70±0.20 g / cm. 3 The mixture was rolled to obtain a negative electrode.
[0089] <90° peel strength (bonding)> The negative electrode obtained above was cut into a strip of 25 mm width, and the composite layer surface of the sample was attached to a double-sided tape fixed to a horizontal surface to prepare a peel test sample. The test sample was dried at 60°C under reduced pressure overnight, and then peeled at 90° at a tensile speed of 50 mm / min to measure the peel strength between the composite layer and the copper foil. The peel strength was high at 12.3 N / m, which was good.
[0090] Examples 2 to 15 and Comparative Examples 1 to 3 A mixture layer composition was prepared by carrying out the same operation as in Example 1, except that the active material, and the carboxyl group-containing crosslinked polymer and carboxyl group-containing non-crosslinked polymer used as the binder were used as shown in Tables 2 and 3. In Example 12, a non-neutralized polyacrylic acid aqueous solution (manufactured by Toagosei Co., Ltd., trade name "Jurimer AC-10L") was added with LiOH·H2O to neutralize the polymer to 90 mol %. In addition, in Examples 4 and 5, natural graphite and silicon particles were stirred at 400 rpm for 1 hour using a planetary ball mill (manufactured by FRITSCH Co., Ltd., P-5), and powdered carboxyl group-containing polymer Li salt R-1 and Aronvis SX were weighed into the resulting mixture as shown in Table 2, and the mixture was thoroughly mixed in advance, and then the mixture layer composition was prepared by carrying out the same operation as in Example 1. The 90° peel strength was evaluated for each mixture layer composition, and the results are shown in Tables 2 and 3.
[0091] [Table 2]
[0092] [Table 3]
[0093] Details of the compounds used in Tables 2 and 3 are shown below. SX: Neutralized salt of non-crosslinked sodium polyacrylic acid (manufactured by Toagosei Co., Ltd., product name "Aronvis SX") AHX: Non-crosslinked polyacrylic acid sodium partially neutralized salt (manufactured by Toagosei Co., Ltd., product name "Aronvis AHX") AC-10L: Non-crosslinked polyacrylic acid (manufactured by Toagosei Co., Ltd., product name "Jurimer AC-10L") T-50: Non-crosslinked polyacrylic acid sodium neutral salt (manufactured by Toagosei Co., Ltd., product name "Aron T-50") "Aronvis," "Jurymer," and "Aron" are registered trademarks of Toagosei Co., Ltd.
[0094] In each example, an electrode was prepared using a secondary battery electrode mixture layer composition according to the present disclosure, and the viscosity of each mixture layer composition (slurry) was sufficiently low, and the coating properties were all good. Focusing on the amount of non-crosslinked polymer having a carboxyl group used, the electrodes of each example were shown to have excellent binding properties compared to electrodes not containing the non-crosslinked polymer (Comparative Example 1, Comparative Example 3) and an electrode using a large amount of non-crosslinked polymer (Comparative Example 2). [Industrial Applicability]
[0095] The binder for secondary battery electrodes of the present disclosure exhibits excellent binding properties in the mixture layer, and therefore, it is expected that a secondary battery equipped with an electrode obtained using the binder will exhibit good durability (cycle characteristics), and is expected to be applied to a secondary battery for vehicles. It is also useful for the use of active materials containing silicon, and is expected to contribute to increasing the capacity of batteries. The binder for secondary battery electrodes of the present disclosure can be suitably used in particular for non-aqueous electrolyte secondary battery electrodes, and is particularly useful for non-aqueous electrolyte lithium ion secondary batteries having high energy density.
Claims
1. A composition for a secondary battery electrode mixture layer comprising a binder, an active material, and water, The binder includes a crosslinked polymer having a carboxyl group and a non-crosslinked polymer having a carboxyl group, The crosslinked polymer contains a structural unit derived from a crosslinkable monomer which is a polyfunctional polymerizable monomer having two or more polymerizable unsaturated groups and / or a polymerizable monomer having a crosslinkable functional group capable of self-crosslinking, and has a degree of neutralization of 75 mol % or more; The composition for a secondary battery electrode mixture layer, wherein the amount of the non-crosslinked polymer used is 1.0 mass % or more and 18.0 mass % or less with respect to the total amount of the crosslinked polymer and the non-crosslinked polymer.
2. The crosslinked polymer contains 50% by mass or more and 100% by mass or less of structural units derived from an ethylenically unsaturated carboxylic acid monomer based on the total structural units of the crosslinked polymer, The composition for a secondary battery electrode mixture layer according to claim 1 , wherein the non-crosslinked polymer contains 50% by mass or more and 100% by mass or less of structural units derived from an ethylenically unsaturated carboxylic acid monomer based on all structural units thereof.
3. A composition for a secondary battery electrode mixture layer as described in claim 1 or 2, wherein the amount of the crosslinkable monomer used in the crosslinked polymer is 0.1 parts by mass or more and 5.0 parts by mass or less per 100 parts by mass of the total amount of the non-crosslinkable monomers.
4. The composition for a secondary battery electrode mixture layer according to any one of claims 1 to 3, wherein the non-crosslinked polymer has a weight average molecular weight of 10,000 or more.
5. A secondary battery electrode comprising a mixture layer formed from the composition for secondary battery electrode mixture layer according to any one of claims 1 to 4 on a surface of a current collector.
Citation Information
Patent Citations
Method for manufacturing electrode plate
JP2017091702A
Binder for lithium cell, composition for producing electrode, and electrode
WO2014065407A1
Secondary cell binder composition
WO2015133424A1
Negative electrode substance for nonaqueous electrolyte secondary battery, negative electrode for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery
WO2016051811A1
Binder for nonaqueous electrolyte secondary battery electrodes and use of same
WO2018043484A1